We Can Quit2 (WCQ2): a community-based intervention on smoking cessation for women living in disadvantaged areas of Ireland—study protocol for a pilot cluster randomised controlled trial - Catherine Hayes (Pilot and Feasibility Studies, 2019)
Abstract Background Tobacco use is the leading cause of preventable death in Ireland with almost 6000 smokers dying each year from smoking-related diseases. The ‘We Can Quit2’ (WCQ2) study is a pilot pragmatic two-arm, parallel-group, cluster randomised trial that aims to explore the feasibility and acceptability of trial processes including recruitment and to estimate parameters to inform sample size estimates needed for an effectiveness trial. This future trial will assess the effectiveness of a community-based smoking cessation intervention for women living in disadvantaged areas on short- and medium-term cessation rates. Methods/design Four matched pairs of districts (eight clusters) selected by area level of deprivation, geographical proximity, and eligibility for free medical services will be randomised to receive either WCQ (behavioural support + access to Nicotine Replacement Therapy (NRT)) delivered over 12 weeks by trained Community Facilitators (CFs) or to a form of usual care, a one-to-one smoking cessation service delivered by Smoking Cessation Officers from Ireland’s national health service, the Health Service Executive (HSE). Within each cluster, 24–25 women will be recruited (97 per arm; 194 in total) in 4 phases with consent obtained prior to cluster randomisation. The outcome measures will assess feasibility and acceptability of trial processes, including randomisation. Outcome data for a future definitive intervention (biochemically validated smoking abstinence) will be collected at end of programme (12 weeks) and at 6 months. WCQ2 has an embedded process evaluation using both qualitative and quantitative methods. This will be conducted (semi-structured client and CF interviews, intervention delivery checklist, and diary) to explore acceptability of trial processes, intervention fidelity, trial context, and implementation. Trial processes will be assessed against domains of the PRECIS-2 wheel to inform a future definitive trial design. Discussion Data from this pilot trial will inform the design and sample size for a full cluster randomised trial to determine the effectiveness of an intervention tailored to disadvantaged women in improving smoking cessation rates. It will provide transferable learning on the systems and implementation strategies needed to support effective design of future pragmatic community-based trials which address health promotion interventions for women in disadvantaged communities. Trial registration Concurrent to publication. Controlled trials ISRCTN74721694.